The DecisionDx-UM Gene Expression Profile Test Provides Risk Stratification and Individualized Patient Care in Uveal Melanoma - Harbour, J. William (Public Library of Science, 2013)
Uveal melanoma (UM) is the most common primary cancer of the eye and has a strong propensity for metastasis. Although there have been many recent improvements in the diagnosis and treatment of UM, and only 2-4% of patients present with detectable metastasis, up to half of patients are at risk for dying of metastatic disease. Clinicopathologic factors are not accurate enough for individualized patient care. Chromosomal alterations have been used for prognostic purposes, but the routine clinical use of these methods is limited by their susceptibility to sampling error resulting from tumor heterogeneity, limited clinical validation, lack of standardized testing platforms, and high technical failure rates. In contrast, the DecisionDx-UM gene expression profile test is a stand-alone platform which requires no other information for maximal prognostic accuracy and which circumvents many of the drawbacks of chromosomal methods through the use of a highly sensitive microfluidics, PCR-based platform that simultaneously measures the expression of 15 carefully selected genes from primary uveal melanoma samples obtained by fine needle biopsy. Low metastatic risk is reported as Class 1, and high metastatic risk as Class 2. The test allows patients to be stratified into risk categories such that high-risk patients can be offered intensive metastatic surveillance and adjuvant therapy while low-risk patients can be spared these interventions. This test is now used as part of the standard of care in many ocular oncology centers.